2022
DOI: 10.1097/brs.0000000000004386
|View full text |Cite
|
Sign up to set email alerts
|

Multifidus Sarcopenia Is Associated With Worse Patient-reported Outcomes Following Posterior Cervical Decompression and Fusion

Abstract: Study Design. Retrospective cohort study. Objective. The present study is the first to assess the impact of paraspinal sarcopenia on patient-reported outcome measures (PROMs) following posterior cervical decompression and fusion (PCDF). Summary of Background Data. While the impact of sarcopenia on PROMs following lumbar spine surgery is well-established, the impact of sarcopenia on PROMs following PCDF has not been investigated. Materials and Methods. We performed a retrospective review of patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 43 publications
1
29
0
Order By: Relevance
“…Patients were classified as Goutalier 0 if there were no visible fat streaks in the muscle, Goutalier 1 if there were minimal fatty streaks in the muscle, Goutalier 2 if there was more muscle present than fat, Goutalier 3 if fat and muscle were present in equal quantity, and Goutalier 4 if more fat was present than muscle. Patients were then further classified as having either mild (Goutalier 0–1), moderate (Goutalier 1.5–2), or severe sarcopenia (Goutalier 2.5–4.0) based upon the Fuchs Modification of the Goutalier grading system 31…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were classified as Goutalier 0 if there were no visible fat streaks in the muscle, Goutalier 1 if there were minimal fatty streaks in the muscle, Goutalier 2 if there was more muscle present than fat, Goutalier 3 if fat and muscle were present in equal quantity, and Goutalier 4 if more fat was present than muscle. Patients were then further classified as having either mild (Goutalier 0–1), moderate (Goutalier 1.5–2), or severe sarcopenia (Goutalier 2.5–4.0) based upon the Fuchs Modification of the Goutalier grading system 31…”
Section: Methodsmentioning
confidence: 99%
“…Patients were then further classified as having either mild (Goutalier 0-1), moderate (Goutalier 1.5-2), or severe sarcopenia (Goutalier 2.5-4.0) based upon the Fuchs Modification of the Goutalier grading system. 31 The occurrence of postoperative complications was determined based on the review of the electronic medical record. Superficial infection was classified as an infection that responded to antibiotics, whereas deep infection was defined as an infection requiring a return to the operating room for irrigation and debridement.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, a novel approach to qualitatively assess paraspinal sarcopenia opportunistically on preoperative magnetic resonance imaging (MRI) has emerged, which has improved both the ease and reliability of sarcopenia assessments 19–23. Using this methodology, recent studies have demonstrated that paraspinal sarcopenia is associated with proximal junctional failures following thoracolumbar fusions and poor patient-reported outcomes (PROMs) and worsening cervical sagittal alignment following posterior cervical decompression and fusion 20,24,25. Despite increasing awareness of the detrimental effects of sarcopenia following spine fusion surgery, the impact of paraspinal sarcopenia on outcomes following cervical laminoplasty remains unknown.…”
mentioning
confidence: 99%
“…[14][15][16] Studies investigating cohorts of patients undergoing posterior cervicothoracic fusions for myelopathy have revealed that severe qualitative sarcopenia is associated with worse patient-reported outcomes, cervical sagittal balance, and junctional alignment. [17][18][19] However, the impact of paraspinal sarcopenia on PJK and PJF following thoracolumbar spine fusion surgery remains unknown. The present study is the first to assess the impact of paraspinal sarcopenia on the development of PJK and PJF following thoracolumbar spine fusion surgery using opportunistic evaluation of paraspinal fatty degeneration on preoperative magnetic resonance imaging (MRI).…”
mentioning
confidence: 99%
“…Sarcopenia is the progressive loss of skeletal muscle mass and is a manifestation of frailty that is not accounted for by other risk stratification methods 14–16. Studies investigating cohorts of patients undergoing posterior cervicothoracic fusions for myelopathy have revealed that severe qualitative sarcopenia is associated with worse patient-reported outcomes, cervical sagittal balance, and junctional alignment 17–19. However, the impact of paraspinal sarcopenia on PJK and PJF following thoracolumbar spine fusion surgery remains unknown.…”
mentioning
confidence: 99%